O homem após Freud e Lacan: sujeito, laço e alteridade - Pereirinha, Filipe (Trabalhos de Antropologia e Etnologia, 2020)
Psychoanalysis is not about the human being as human being, but as a Subject. It is the proposal of Lacan following Freud. But what is the Subject for Lacan? And why he invents the «Parlêtre» term to replace the Subject? Here are some of the questions that guide us and which we intend to answer.